New nighttime light landscape metrics for analyzing urban-rural differentiation in economic development at township: A case study of Fujian province, China. (January 2023) - Chen, Zuoqi; Yu, Siyi; You, Xiaojun; Yang, Chengshu; Wang, Congxiao; Lin, Juan; Wu, Wenting; Yu, Bailang
Abstract: The urban-rural difference in economy is a key indicator of urban sustainability and socio-economic development, especially when the rapid urbanization has taken place in China. Scientific understanding of the urban-rural economy difference will help the future urbanization process and policy decisions. Different from the traditional analysis based on statistical data, we have conceptualized the novel nighttime light landscape metrics, by analogy to traditional landscape metrics, to reveal the rural and urban economic development, as well as their differences from multi-perspectives (e.g., economic volume and economic expansion). Taking all towns in Fujian province as examples, we found from 2000 to 2020 the urban economic development presents a decoupling between the economic volume and economic space, which satisfies the criteria of high-quality urbanization. The rural economy has a rapid development mainly via the rural construction and structural transformation, which furthermore caused the differences between the coastal and inland urban-rural economic differentiation. Our empirical results indicate the novel nighttime light landscape metrics are valuable indicators to facilitate the analysis of economy distribution and evolution. Also, owing to the conceptualization of traditional landscape metrics, the nighttime light landscape metrics can be further enriched to reveal more information of economic development, even of other fields. Highlights: The nighttime light landscape metrics were proposed to reveal economic development. A narrowing rural-urban gap of economic development was found in Fujian. The economic volume and space tend to be decoupled in urban-related towns. The economy of the rural-related town is more homogeneous than that of the urban-related town. The urban-rural differences in coastal and inland cities are various from different perspectives.